American Justice 2014 - Garrett Epps (University of Pennsylvania Press, 2014)
In many ways, the US Supreme Court is as determinedly opaque as the National Security Agency. Though it maintains a talented public-information staff, the institution itself takes no responsibility whatsoever for explaining itself to the public. The product of the courtâ€™s workâ€” its oral argument transcripts, opinions, and ordersâ€”is made available promptly. The real work of the justices, howeverâ€”deciding which cases to accept, discussing who should win cases and why, picking justices to write opinions, and criticizing the successive draftsâ€”takes place behind a veil of secrecy that, for most of the court staff and law clerks, would be professional death to pierce. Years after a justice dies, papers in a library may show how and why the court decided some issue. Historians revel in these sources, but for lawyers and citizens who must live today, they provide little help for understanding what the court is up to. The courtâ€™s secrecy is only part of the reason it is ill understood. A nine-member body has no â€œintentionâ€ the way an individual has. Thus the Supreme Court may not really â€œknowâ€ why it is doing what it is doing. Each decision is the sum of many calculations by lawyers, lower courts, and justices to shape issues in a certain way that produces a result. In time, this result may come to seem inevitable, but it almost certainly was not from the outset of the issue. (Think of the courtâ€™s iconic school desegregation decision in Brown v. Board of Education. History shows us a bitterly divided court grappling with the issueâ€”until a unanimous opinion improbably emerged.) Wherever the justices may think they are going, the court is quite likely to end up somewhere else, blown off course by the winds of judicial politics. â€œIt is quite true what philosophy says; that life must be understood backwards,â€ the philosopher SÃ¶ren Kierkegaard wrote in 1843. â€œBut then one forgets the other principle: that it must be lived forwards.â€